Academic Writing Course. Structure, planning and scripting of the text - Torres-Salinas, Daniel (Infonomy, 2025)
This article, part of the Academic Writing Course, addresses the structured planning of scientific texts and the efficient distribution of content. The IMRYD model is examined as the standard structure in academic writing, detailing its sections and their length according to the discipline. Strategies are presented to establish a precise outline, determining the number of paragraphs and their thematic content, as well as the relationship between text length and its functional role in the discourse. Additionally, the importance of coherence and cohesion between paragraphs is emphasized to ensure a clear and well-structured academic narrative. Finally, a paragraph-based planning template is proposed to efficiently and systematically organize the writing process of a scientific article.
Keywords: Academic writing; IMRYD structure; Scientific discourse; Paragraph organization